A speech recognition system based on structure equivalent fuzzy neural network trained by firefly algorithm - Tahereh Hassanzadeh; Karim Faez; Golnaz Seyfi (Institute of Electrical and Electronics Engineers (IEEE), 2012)
Link to publisher's homepage at http://ieeexplore.ieee.org/